ABOUT PUBLIC APPEALS AND THE PUBLIC JUSTIFICATION OF TERRORISM - Nikolay N. Lysov (Вестник Северо-Кавказского федерального университета)
In article the question of validity of criminalization of public appeals and a public justification of terrorist crimes is considered. Made a number of remarks on need of change of art. 205.2 of the criminal code of Russian Federation.